Mobile application as a tool for urban traffic data collection and generation to Advanced Traveler Information Systems using Wi-Fi networks available in urban centers - Dezani, Henrique; Damiani, Furio; Marranghello, Norian [UNESP]; Viudes, Ulysses; Parra, Icaro Augusto; IEEE (Ieee, 2012)
This paper presents an Advanced Traveler Information System (ATIS) developed on Android platform, which is open source and free. The developed application has as its main objective the free use of a Vehicle-to-Infrastructure (V2I) communication through the wireless network access points available in urban centers. In addition to providing the necessary information for an Intelligent Transportation System (ITS) to a central server, the application also receives the traffic data close to the vehicle. Once obtained this traffic information, the application displays them to the driver in a clear and efficient way, allowing the user to make decisions about his route in real time. The application was tested in a real environment and the results are presented in the article. In conclusion we present the benefits of this application.